Tunable laser optics - Duarte, F. J. (Elsevier Academic Press, 2003)
Chapters will provide self-contained treatment of the topic as much as possible to allow the reader to go directly to the appropriate chapter to deal with a particular topic of concern. This sharp focus is necessary to maintain the emphasis, and to make this a practical reference. The knowledge and experience will integrate aspects of laser oscillators, laser amplifiers, laser systems, engineering of rugged laser cavities, design and engineering of laser-based instrumentation, and design of highly reliable laser systems for material processing applications. * Provides a sharp focus practical aspects of reference material. * Offers an approach that will be simple, direct, and focused only on lasers and optics * Integrates aspects of laser oscillators, laser amplifiers, laser systems, engineering of rugged laser cavities, design and engineering of laser-based instrumentation, and design of highly reliable laser systems for material processing applications.
Keywords: Lasers.; Electrooptics.; elektronické knihy; electronic books